Magnetic parameters of SrFe12O19 sintered from a mixture of nanocrystalline and micron-sized powders - Shashanka, H. M.; Anantharamaiah, P. N.; Joy, P. A. (Ceramics International, 2019)
Obtaining higher magnetic parameters is essential for high-power sintered strontium ferrite (SrFe12O19) for various applications. A novel approach has been made to improve the magnetic parameters of sintered strontium ferrite by making self-composites from nano and micron-sized powders. Powders with two different weight ratios (50 wt% nano:50 wt% micron and 75 wt% nano:25 wt% micron) were mixed together, compacted and sintered at 1200 degrees C for 1 h. For a self-composite of 75 wt% nano and 25 wt% micron-sized powders, coercivity (H-c) of 3076 Oe has been obtained, larger than the values for the sintered compacts from the component powders. The present study suggests that the magnetic parameters of sintered SrFe12O19 can be improved by making self-composite comprising of nanocrystalline and micron-sized powders.
Keywords: Ceramics; Magnetic materials; microstructures; Self-composites; strontium ferrite